Pengaruh Pemberian Jus Nanas dan Plum terhadap Penyembuhan Luka Perineum Pada Ibu Postpartum - Marcelina, Lina Ayu; Arum Sari, Retno (Jurnal Kesehatan Holistic, 2025)
Background : Perineal wound healing is influenced by various factors, one of which is nutritional status. Consumption of protein and vitamins A and C is essential. Many products are available to accelerate wound healing, but there have not been many studies on the role of pineapple and plum juice in wound healing, especially in the postpartum mother's perineum. Objective : To investigate the effect of giving pineapple and plum juice on perineal wound healing in postpartum mothers. Methods : The design of this study was quasi-experimental with a pretest-posttest design with a control group. The sampling technique was accidental sampling involving 66 spontaneous postpartum mothers with episiotomy wounds on the first day. The instruments used include demographic data and wound healing observation sheets. Results : The mean age of respondents in the control and experimental groups was 28 years (84.8%), highly educated (93.9%), and multiparous (69.7%). Giving pineapple and plum juice had a significant effect on perineal wound healing in postpartum mothers (p < 0.001). Conclusion : Pineapple and plum juices contribute to the healing of perineal wounds. It is hoped that mothers can apply pineapple and plum juice interventions by making their juice to help the perineal suture wound healing process. Keyword : episiotomy; perineal wound; pineapple juice; plums; postpartum